2010
DOI: 10.1021/om100038f
|View full text |Cite
|
Sign up to set email alerts
|

(β-Diketiminato)dimethylgold(III): Synthesis, Structure, and Reactivity

Abstract: The reaction between [Me 2 AuCl] 2 and the lithium salt of a β-diketimine, [HC{C(Me)N(C 6 H 3 -2, 6-Me 2 )} 2 Li], yields the neutral Au(III) compound [HC{C(Me)N(C 6 H 3 -2,6-Me 2 )} 2 AuMe 2 ] (1). Compound 1 reacts with 1 equiv of triflic acid (HOTf) at -78 °C to provide the cationic AuTreatment of 1 with 2 equiv of HOTf results in the displacement of Me 2 AuOTf and formation of the β-diketiminato triflate salt [HC{C(Me)NH(C 6 H 3 -2,6-Me 2 )} 2 ][OTf] (3). Compound 1 reacts with I 2 to yield the cation [HC(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
19
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 51 publications
4
19
0
Order By: Relevance
“…155 The agostic nature of the interaction of the bridging methyl was determined partly based on analysis of its JCH coupling constant, which, at ca. 125 Hz, according to the authors, was deemed significantly lower, than that found for other methyl fragments (135)(136)(137)(138)(139)(140). This was attributed to thermal averaging of the normal C-H coupling of ca.…”
Section: Scheme 29 Examples Of Methyl Bridged Homobimetallic Complexementioning
confidence: 79%
“…155 The agostic nature of the interaction of the bridging methyl was determined partly based on analysis of its JCH coupling constant, which, at ca. 125 Hz, according to the authors, was deemed significantly lower, than that found for other methyl fragments (135)(136)(137)(138)(139)(140). This was attributed to thermal averaging of the normal C-H coupling of ca.…”
Section: Scheme 29 Examples Of Methyl Bridged Homobimetallic Complexementioning
confidence: 79%
“…Scheme 43) 109,111,113,[183][184][185][186][187]. Overall, these remarkable examples demonstrate the coordinative versatility of the BDI ligands.Additionally, a variety of p-block electrophiles have been shown to react with (BDI)Li salts at the γ-carbon of the BDI backbone to form diverse structures of which selected examples are reproduced in Scheme 44 70,[188][189][190][191][192][193][194][195].…”
mentioning
confidence: 78%
“…Substituting the γ-Me group by a γ-H leads to alkylation of the BDI γ-carbon and yields the corresponding cationic diimine complex featuring a C-C bond between a trityl fragment and the BDI gamma-carbon (Scheme 47bottom). 111 It is remarkable that in these last two examples the methine carbon of the BDI ligand is the preferred site of electrophilic attack compared to the Zn-Me and Au-Me bonds which remain inert. 111 It is remarkable that in these last two examples the methine carbon of the BDI ligand is the preferred site of electrophilic attack compared to the Zn-Me and Au-Me bonds which remain inert.…”
Section: Scheme 42 Structures Of Ti and Cr Bdi Derivatives Featuring mentioning
confidence: 98%
See 1 more Smart Citation
“…The AuÀC Me bond lengths in 3-BArf are 2.049(4) and 2.055(4) , quite typical for cationic Au III Me 2 fragments with relatively weak donor ligands trans to the methyl groups. [45,46] The structures of [(cod)AuMe 2 + ] and [(cod)PtMe 2 ], optimized at the DFT level with the hybrid PBE0 functional and quasi relativistic effective core potential (ECP) for Au (see computational details [47] ), indispensable for representing the structures and reactivity of Au complexes, [57,58] are in excellent agreement with the solid-state structures ( Table 1 and the Supporting Information). In particular, the calculations reproduce very well the nonequivalence of the two M À C cod bond lengths to the same C = C, and the larger difference between these distances for Au versus Pt.…”
mentioning
confidence: 79%